2019
DOI: 10.1200/jco.2019.37.15_suppl.1040
|View full text |Cite
|
Sign up to set email alerts
|

Alpelisib (ALP) + endocrine therapy (ET) in patients (pts) with PIK3CA-mutated hormone receptor-positive (HR+), human epidermal growth factor-2-negative (HER2-) advanced breast cancer (ABC): First interim BYLieve study results.

Abstract: 1040 Background: In the phase 3 SOLAR-1 study, ALP + fulvestrant (FUL) improved PFS in pts with HR+, HER2– ABC with a PIK3CA mutation overall and in the small group of pts with prior cyclin-dependent kinase 4/6 inhibitor (CDKi) use. We report interim data from the BYLieve study in pts with PIK3CA-mutated ABC and prior CDKi exposure. Methods: BYLieve is an ongoing, phase 2, open-label, non-comparative study of ALP 300 mg QD + ET in men and women with PIK3CA-mutated HR+, HER2– ABC whose disease progressed on/af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…As for Alp, small prospective trials published before the SOLAR-1 study evaluated the Let/Alp or Fulv/Alp combinations in patients with HR+ HER2− mBC progressing after previous ET. Consistent with SOLAR-1 results, these studies reported an incidence of G3/G4 hyperglycemia and rash in the 10-38.1% and 8-27.8% ranges, respectively, with longer mPFS in patients with PIK3CA-mutated neoplasms (Table 5) [30,35,51].…”
Section: Other Prospective Studies Investigating Eve or Alpsupporting
confidence: 81%
“…As for Alp, small prospective trials published before the SOLAR-1 study evaluated the Let/Alp or Fulv/Alp combinations in patients with HR+ HER2− mBC progressing after previous ET. Consistent with SOLAR-1 results, these studies reported an incidence of G3/G4 hyperglycemia and rash in the 10-38.1% and 8-27.8% ranges, respectively, with longer mPFS in patients with PIK3CA-mutated neoplasms (Table 5) [30,35,51].…”
Section: Other Prospective Studies Investigating Eve or Alpsupporting
confidence: 81%
“…The safety profile in this cohort was consistent with the known safety profile of alpelisib [1,18]; the most commonly experienced all-grade adverse events (AEs) were diarrhea (59.8%), hyperglycemia (58.3%), nausea (45.7%), fatigue (29.1%), decreased appetite (28.3%), rash (28.3%), and stomatitis (26.8%), with no new safety signals observed. Overall AE-related discontinuations in this cohort were 20.5% [16,17].…”
Section: Introductionmentioning
confidence: 81%
“…The Phase II, open-label, multicenter, noncomparative, 3-cohort BYLieve trial (NCT03056755) is the first study designed to assess the safety and efficacy of alpelisib combined with ET in patients with PIK3CA-mutated HR+, HER2-ABC and who progressed on/after prior CDK4/6i-based therapy. BYLieve confirmed efficacy and safety of alpelisib combined with fulvestrant in patients with confirmed PIK3CAmutated disease who received a CDK4/6i with AI as immediate prior therapy (Cohort A) [16,17]. The primary endpoint of the trial was met, as 50.4% (95% CI, 41.2%-59.6%) of patients in Cohort A were alive without disease progression at 6 months, with the lower bound of the CI being greater than the prespecified threshold of 30%.…”
Section: Introductionmentioning
confidence: 82%
“…ByLieve, a phase 2 multicenter, open-label, two-cohort, noncomparative study of alpelisib + fulvestrant or letrozole, including patients who progressed on or after CDKi + AI or fulvestrant (metastatic setting) or with ≤1 line of previous chemotherapy (adjuvant or advanced setting) with the primary endpoint of patients alive and without disease progression at 6 months, will be determinant to this question. Although at the first interim analysis, the fulvestrant cohort seems to be better than the letrozolo cohort, the data are still immature [ 63 ].…”
Section: Future Perspectivesmentioning
confidence: 99%